Analysis of Student Errors in Solving Problems on Three-Dimensional Shapes with Flat Surfaces: A Qualitative Study on Eighth-Grade Students - Febriyanti, Wiwid; Wahyuddin, Wahyuddin; Mutmainnah, Mutmainnah (International Journal of Geometry Research and Inventions in Education, 2024)
This study analyzes errors made by eighth-grade students in solving problems involving three-dimensional geometric shapes with flat surfaces and examines the factors causing these errors. Using a qualitative descriptive approach, three students with varying error levels (high, medium, low) were selected for analysis through written tests and in-depth interviews. Data were processed using the Miles and Huberman model: data reduction, data presentation, and conclusion drawing. Findings identified four main error types: factual, conceptual, principle, and operational. High-error students mainly struggled with conceptual understanding and operations, while low-error students primarily made operational errors. The results highlight that weak conceptual understanding and cognitive overload were the key factors in these errors. This study implies that teaching strategies should enhance both conceptual and procedural knowledge, utilizing interactive and manipulative learning methods to reduce cognitive load and improve student performance in geometry.